β-Endorphin Mediates the Development and Instability of Atherosclerotic Plaques - Taisuke Okano; Kengo Sato; Remina Shirai; Tomomi Seki; Koichiro Shibata; Tomoyuki Yamashita; Ayaka Koide; Hitomi Tezuka; Yusaku Mori; Tsutomu Hirano; Takuya Watanabe (International Journal of Endocrinology)
β-Endorphin, an endogenous opioid peptide, and its μ-opioid receptor are expressed in brain, liver, and peripheral tissues. β-Endorphin induces endothelial dysfunction and is related to insulin resistance. We clarified the effects of β-endorphin on atherosclerosis. We assessed the effects of β-endorphin on the inflammatory response and monocyte adhesion in human umbilical vein endothelial cells (HUVECs), foam cell formation, and the inflammatory phenotype in THP-1 monocyte-derived macrophages, and migration and proliferation of human aortic smooth muscle cells (HASMCs) in vitro. We also assessed the effects of β-endorphin on aortic lesions in Apoe−/− mice in vivo. The μ-opioid receptor (OPRM1) was expressed in THP-1 monocytes, macrophages, HASMCs, HUVECs, and human aortic endothelial cells. β-Endorphin significantly increased THP-1 monocyte adhesion to HUVECs and induced upregulation of intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and E-selectin via nuclear factor-κB (NF-κB) and p38 phosphorylation in HUVECs. β-Endorphin significantly increased HUVEC proliferation and enhanced oxidized low-density lipoprotein-induced foam cell formation in macrophages. β-Endorphin also significantly shifted the macrophage phenotype to proinflammatory M1 rather than anti-inflammatory M2 via NF-κB phosphorylation during monocyte-macrophage differentiation and increased migration and apoptosis in association with c-jun-N-terminal kinase, p38, and NF-κB phosphorylation in HASMCs. Chronic β-endorphin infusion into Apoe−/− mice significantly aggravated the development of aortic atherosclerotic lesions, with an increase in vascular inflammation and the intraplaque macrophage/smooth muscle cell ratio, an index of plaque instability. Our study provides the first evidence that β-endorphin contributes to the acceleration of the progression and instability of atheromatous plaques. Thus, μ-opioid receptor antagonists may be useful for the prevention and treatment of atherosclerosis.